“APERTURA-APRETURA-CERRADURA”: CRISIS, SOCIAL PROTESTS AND LIMITED OPENING 1981-1985. - Assis dos Santos, Eric (Revista de Historia Social y de las Mentalidades, 2024)
This article aims to analyze the process of  liberalization limited Pinochet and the Chilean  Armed Forces in 1981-1985. Through reports,  speeches, press and official documents, we  targeted identifying actors and circumstances that  created the first good chance of overthrowing  the Chilean dictatorship. To this end, we try to  analyze the process of democratic transition from  a perspective that combines social demands of  the 1983-1984 protests and internal debates of  the Pinochet government.
Keywords: Dictatorship; Protests; Democratic transition